大気二酸化炭素濃度の増加が炭酸カルシウム合成生物に与える影響の解明 - 栗原, 晴子; Kurihara, Haruko (栗原晴子, 2010)
科研費番号: 20710008 2008年度～2009年度科学研究費補助金（若手研究(Ｂ)）研究成果報告書 研究概要（和文）：大気二酸化炭素濃度の増加に伴い海では、海水のpHおよび炭酸カルシウム飽和度の低下する酸性化現象が予測されている。近年、海水が酸性化するとウニや貝類など炭酸カルシウムを合成する生物の殻や骨の形成不全が引き起こされることが明らかにされつつあるが、その影響の機構は未だ解明されていない。本研究では異なるpH環境下でウニ幼生を飼育し、骨の形成に関わる遺伝子の発現への影響を探った結果、Ca^<2+>の輸送に関わる遺伝子がpHに依存して低下することが明らかになった。従って、酸性化は遺伝子レベルで生物の石灰化機構に影響を及ぼすことが初めて示唆された。 研究概要（英文） : Increasing atmospheric CO2 is predicted to decrease the seawater pH and calcium carbonate saturation state and acidify the oceanic seawater. Recent studies revealed that ocean acidification cause malformed shells and spicules on marine calcifiers including sea urchins and bivalves. However, the mechanism of these effects is still unclear. In this present study, we evaluated the expression of skeletogenesis related genes on sea urchins larvae cultured under different pH conditions. As a result we cleared that the expression of the gene known to be related on Ca2+ transportation decreased with pH decrease. There results first demonstrated that ocean acidification can affect the calcification process of marine organisms at a molecular biological level. 研究報告書 http://purl.org/coar/resource_type/c_18ws